Tecnologias verdes: mecanismo de efetivação da Política Nacional de Resíduos Sólidos aplicadas ao setor agrícola. - Oliveira, Greice Kelly Lourenço Porfírio de (2017)
This present study has as its general theme, the study of environment friendly green technologies, which were applied to rural activities such as mechanisms of effectiveness pertaining to the objectives of the National Policy of Solid Residue adhering to the following line of study: Agro-Food Law, Territories and Development. The study will begin from law 12.305/10 denominated as National Policy of Solid Residue. In this bias, a reflection shall be made about the use of green technologies, such as techniques that are able to meet the objectives that were created by the National Policy of Solid Residue, in reference to incentives towards the creation of clean technology, treatment, reutilization and adequate disposal of solid residue in the agriculture sector; which are described in article 7 of the referred law, aiming towards harmony in the national and sustainable technological development.